Reshaping Urbanization in Rwanda : Economic and Spatial Trends and Proposals - World Bank Group (World Bank, Washington, DC, 2017)
Rwanda has demonstrated a remarkable performance in economic growth and poverty reduction in the past decade and a half. With urbanization as an explicit developmental strategy, the government has indeed made significant efforts to prepare a solid foundation on which urban development can take off. The objective of this report is to inform the government’s policies and strategies on urbanization as a driver of economic development, job creation, and poverty reduction, through the following four stand‐alone but closely related notes. Note 1 examines Rwanda’s urbanization process since 2002 by analyzing satellite images and various other sources. Note 2 analyzes internal migration patterns of Rwandan households, mainly based on the last two household surveys, and discusses the main drivers or reasons for migration. Note 3 explores whether and to what extent urbanization, in the sense of increased density and enhanced connectivity has resulted in job creation and poverty reduction in Rwanda. Note 4 provides a detailed analysis of the core secondary cities of the country, discussing their expansion in terms of urban area and population, economic profiles and potential, access to services, and urban development plans. A separate note has been prepared to provide an alternative definition of urbanization in Rwanda, addressing the on the constraints associated with the current definition of urbanization. This Synthesis Note presents the key findings, messages, and recommendations of the overall work.